Transforming the Fan Experience through Livestreaming: A Conceptual Model. Issue 2 (4th May 2021) - Wymer, Sarah; Naraine, Michael L.; Thompson, Ashleigh-Jane; Martin, Andrew J.
Abstract: The purpose of this case study research was to explore how Queensland Rugby League (QRL) used a Facebook brand page, for the Queensland Maroons, and incorporated livestreaming throughout the 2017–2018 State of Origin seasons. Specifically, this study sought to understand managerial perspectives regarding interactive advertising within digital sports marketing strategy encompassing livestreaming and the extent to which it may impact fan engagement. This research utilized a multimethod case study approach involving a content analysis of Facebook, complemented by two semistructured interviews with the organization's digital staff. The findings revealed livestreaming can be an engaging proposition when it provides exclusive content that allows fans to experience authentic insights into the rituals and traditions of their favorite sports team and athletes in real time. Furthermore, three unique management livestreaming experiences were identified: planning, organization, and delivery (POD). As a response, a conceptual POD model has been created that reevaluates the opportunities for fan engagement adapted from previous research findings (Haimson and Tang 2017 ; Naraine and Karg 2019). This model is important for sports organizations when considering livestreaming, as there may be unique opportunities to focus on interactive advertising and, thus, to develop awareness and the fan-to-fan and fan-to-athlete/sports organization/team relationship.